Características físico-químicas do grão de cultivares de arroz em função da adubação nitrogenada - Checchio Mingotte, Fabio Luiz [UNESP]; Hanashiro, Renata Kimie; Fornasieri Filho, Domingos [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Rice (Oryza sativa L.) stands out as a staple food of the world population due to important nutritional properties. However, rice physico-chemical parameters vary according to genotype and management, for example, the use of nitrogen fertilizer. The aim of this work was to evaluate physico-chemical parameters of grains from thirteen cultivars of upland rice under supplemental sprinkler irrigation and fertilized with different nitrogen rates by topdressing (0, 40, 80, 120 and 160 kg ha(-1)). Parameters such as milling efficiency, commercial grade, gelatinization temperature, as well as total nitrogen and crude protein contents of grains were evaluated. Nitrogen fertilization positively influences the whole grain yield, especially IAC 25 and BRS Colosso. BRS Aroma, IAC 202, IAC 500, BEST 2000, Curinga and Baldo have a high percentage of broken grains. The cultivars Baldo and Carnaroli (appropriate for Italian cuisine), IAC 25 and Caiapo are classified as long grain and the others, as long-thin. The cultivars, except CIRAD 141, displayed grain gelatinization temperature between intermediate and low, providing quick cooking. The grain content protein varies among cultivars, and it can be increased with nitrogen fertilization.
Physico-chemical parameters of rice cultivars fertilized with nitrogen
Keywords: Oryza sativa L.; Nitrogen; nutritional quality; alkali test